A more efficient way to shape metal-organic framework (MOF) powder materials for hydrogen storage applications. (13th April 2015) - Ren, Jianwei; Musyoka, Nicholas M.; Langmi, Henrietta W.; Swartbooi, Ashton; North, Brian C.; Mathe, Mkhulu
Abstract: Shaping of Zr-MOF powder material into spherical pellets with diameters of 0.5–15 mm in the presence of 10 wt.% sucrose as a binder was successfully demonstrated using a granulator. Zr-MOF pellets were produced in a kilogram batch within 30 min operation time. This granulation approach is a more efficient way to shape MOF-type powder materials into application-specific configurations compared to the mechanical pressing method. The pellets could be conveniently packed in a small hydrogen storage tank. The physical degradation characteristics of the Zr-MOF pellets were studied by drop test and simulated tumbler drum test. The results showed zero breakage of the pellets after 70 consecutive drops at a height of 0.5 m and 5% breakage after 60 min of tumbling time at a speed of 25 rpm. Although the compromised value of the surface area led to a decreased hydrogen storage capacity, this shaping approach still holds promise given an appropriate choice of binder. Highlights: Powder Zr-MOF material was shaped into pellets (0.5–15 mm) using sucrose as binder. The diameter of pellets can be controlled by shaping time. The Zr-MOF pellets can be produced in kilograms order within 30 min operation time. Drop and tumbling tests were used to evaluate the mechanical strength of the pellets. The process facilitates the transition of MOF powders from lab to applications.